Grounds of Existence in Kant’s New Elucidation - Nikkarla, Markus (Con-Textos Kantianos. International Journal of Philosophy, 2020)
Kant wrote in the Only Possible Argument in Support of a Demonstration of the Existence of God (1763), that existence is not a predicate of things. In this paper I argue that his thinking is based on the same view already in the New Elucidation, written in 1755. In this early text, Kant carefully distinguishes the grounds of existence from grounds of knowledge and argues that contingent existence always has an antecedently determining ground. I examine how Kant thinks that God contains the extralogical grounds that are required for things not only to exist but also to undergo change and interact with other things. I also consider briefly how the New Elucidation could help us to understand Kant’s mature view on the grounds of existence.